Multiwavelength Study of a Hyperluminous X-Ray Source near NGC 6099: A Strong IMBH Candidate - Yi-Chi Chang; Roberto Soria; Albert K. H. Kong; Alister W. Graham; Kirill A. Grishin; Igor V. Chilingarian (The Astrophysical Journal)
We report on the intriguing properties of a variable X-ray source projected at the outskirts of the elliptical galaxy NGC 6099 ( d  ≈ 139 Mpc). If truly located near NGC 6099, this is a hyperluminous X-ray source that reached an X-ray luminosity L _X  ≈ a few times 10 ^42 erg s ^−1 in 2012 February (XMM-Newton data), about 50–100 times brighter than in 2009 May (Chandra) and 2023 August (XMM-Newton). The X-ray spectrum was soft at all three epochs, with a thermal component at kT  ≈ 0.2 keV and a power-law photon index >3. Such properties make it a strong candidate for an intermediate-mass black hole (IMBH). We also discovered a point-like, blue optical counterpart ( m _g _,Vega  ≈ 24.7 mag, M _g _,Vega  ≈ −11.2 mag), from images taken by the Canada–France–Hawaii Telescope and later confirmed with Hubble Space Telescope observations. The optical continuum can be modeled as stellar emission from a compact star cluster or an X-ray-irradiated accretion disk, consistent with the IMBH scenario. We discuss alternative explanations for the nature of this system. A possible scenario is tidal stripping of an orbiting star, with repeated X-ray outbursts every few years. An alternative possibility is that the thermal X-ray emission seen in 2009 was from shocked gas in the self-intersecting tidal stream during the rising phase of a tidal disruption event, while the 2012 and 2023 emissions were from the fully formed accretion disk.